Anti-Biofilm Coatings Based on Chitosan and Lysozyme Functionalized Magnetite Nanoparticles - Vera Alexandra Spirescu; Adelina-Gabriela Niculescu; Ștefan Slave; Alexandra Cătalina Bîrcă; Gabriela Dorcioman; Valentina Grumezescu; Alina Maria Holban; Ovidiu-Cristian Oprea; Bogdan Ștefan Vasile; Alexandru Mihai Grumezescu; Ionela Cristina Nica; Miruna Silvia Stan; et al. (MDPI AG, 2021)
Biofilms represent a common and increasingly challenging problem in healthcare practices worldwide, producing persistent and difficult to manage infections. Researchers have started developing antibiotic-free treatment alternatives in order to decrease the risk of resistant microbial strain selection and for the efficient management of antibiotic tolerant biofilm infections. The present study reports the fabrication and characterization of magnetite-based nanostructured coatings for producing biofilm-resistant surfaces. Specifically, magnetite nanoparticles (Fe3O4) were functionalized with chitosan (CS) and were blended with lysozyme (LyZ) and were deposited using the matrix-assisted pulsed laser evaporation (MAPLE) technique. A variety of characterization techniques were employed to investigate the physicochemical properties of both nanoparticles and nanocoatings. The biological characterization of the coatings assessed through cell viability and antimicrobial tests showed biocompatibility on osteoblasts as well as antiadhesive and antibiofilm activity against both Gram-negative and Gram-positive bacterial strains and no cytotoxic effect against human-cultured diploid cells.